![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
7.5*2.13-2.5*2.39简便方法?
展开全部
7.5x2.13-2.5x2.39简便运算:
7.5x2.13-2.5x2.39
=2.5x3x2.13-2.5x2.39
=2.5x(3x2.13)-2.5x2.39
=2.5x6.39-2.5x2.39
=2.5x(6.39-2.39)
=2.5x4
=10
7.5x2.13-2.5x2.39
=2.5x3x2.13-2.5x2.39
=2.5x(3x2.13)-2.5x2.39
=2.5x6.39-2.5x2.39
=2.5x(6.39-2.39)
=2.5x4
=10
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2.5*3*2.13-2.5*2.39=2.5*(6.39-2.39)=2.5*4=10
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2.5*3*2.13-2.5*2.39=2.5*(6.39-2.39)=2.5*4=10
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
原式=2.5×3×2.13-2.5×2.39
=2.5×(2.13×3-2.39)
=2.5×(6.39-2.39)
=2.5×4
=10供参考吧
=2.5×(2.13×3-2.39)
=2.5×(6.39-2.39)
=2.5×4
=10供参考吧
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询